Остров погибших кораблей - Беляев Александр Романович (Библиотека приключений продолжается..., 1994)
Экземпляры: ф. 4 (20120209) / Инвентарный номер: 98092 / Цена: 20 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 44 / ББК: 84(2Рос=Рус)6